Personnel Administration in the Digital Era According to the Noble Eightfold Path of Administrators in Primary Schools under the Na-o Si Muang Chai Educational Quality Group, Loei Primary Educational Service Area Office 1: Personnel Administration in the Digital Era According to the Noble Eightfold Path of Administrators in Primary Schools under the Na-o Si Muang Chai Educational Quality Group, Loei Primary Educational Service Area Office 1 - Ngamsuay, Rungtiwa; Hassarin, Prasong; Phrakhru Pariyattikhunrangsi (RATANABUTH JOURNAL, 2026)
The objectives of this mixed-methods research were: 1) to investigate the state of personnel administration in the digital era among primary school administrators in the Na Ao Si Mueang Chai Educational Quality Group, under the Loei Primary Educational Service Area Office 1; 2) to examine the methods of personnel administration based on the Noble Eightfold Path among these administrators; and 3) to propose guidelines for personnel administration based on the Noble Eightfold Path for the aforementioned administrators. The quantitative sample consisted of 61 participants comprising 5 administrators and 56 teachers from schools within the Na Ao Si Mueang Chai Educational Quality Group. The research instruments utilized were questionnaires and interview forms. Quantitative data were analyzed using percentage, mean, standard deviation, and t-test. For the qualitative study, data were collected through in-depth interviews with 7 key informants, selected via purposive sampling based on specific qualifications. The research findings were as follows: 1) The overall state of personnel administration in the digital era was at the highest level, 2) The overall methods of personnel administration in the digital era based on the Noble Eightfold Path were rated at the highest level. And 3) The proposed guidelines for personnel administration based on the Noble Eightfold Path suggest that administrators should foster personnel development and organizational success by ensuring the performance evaluation process is transparent, equitable, and mutually beneficial to both the employees and the organization. Administrators should establish concrete, measurable goals and conduct periodic monitoring to track progress. Providing immediate and constructive feedback is essential to help personnel continuously improve and develop themselves. Furthermore, the organization should facilitate training programs to enhance staff skills in alignment with organizational needs. Finally, cultivating a work environment grounded in accountability, integrity, and fairness.